Digitizing the thermal and hydrological parameters of land surface in subtropical China using AMSR-E brightness temperatures. Issue 7 (3rd July 2017) - Su, Yongxian; Chen, Xiuzhi; Su, Hua; Liu, Liyang; Liao, Jishan
ABSTRACT: Digitizing the land surface temperature ( Ts ) and surface soil moisture ( mv ) is essential for developing the intelligent Digital Earth. Here, we developed a two parameter physical-based passive microwave remote sensing model for jointly retrieving Ts and mv using the dual-polarized Tb of Aqua satellite advanced microwave scanning radiometer (AMSR-E) C-band (6.9 GHz) based on the simplified radiative transfer equation. Validation using in situ Ts and mv in southern China showed the average root mean square errors (RMSE) of Ts and mv retrievals reach 2.42 K ( R 2 = 0.61, n = 351) and 0.025 g cm −3 ( R 2 = 0.68, n = 663), respectively. The results were also validated using global in situ Ts ( n = 2362) and mv ( n = 1657) of International Soil Moisture Network. The corresponding RMSE are 3.44 k ( R 2 = 0.86) and 0.039 g cm −3 ( R 2 = 0.83), respectively. The monthly variations of model-derived Ts and mv are highly consistent with those of the Moderate Resolution Imaging Spectroradiometer Ts ( R 2 = 0.57; RMSE = 2.91 k) and ECV_SM mv ( R 2 = 0.51; RMSE = 0.045 g cm −3 ), respectively. Overall, this paper indicates an effective way to jointly modeling Ts and mv using passive microwave remote sensing.